Comparison of MTA versus Biodentine in Apexification Procedure for Nonvital Immature First Permanent Molars: A Randomized Clinical Trial - Yasser Alsayed Tolibah; Chaza Kouchaji; Thuraya Lazkani; Ibrahim Ali Ahmad; Ziad D. Baghdadi (MDPI AG, 2022)
This study aimed to evaluate the radiological and clinical outcomes of Biodentine apical plugs compared to mineral trioxide aggregate (MTA) in treating immature molars with apical lesions in children. Materials and Methods: Thirty immature roots of 24 permanent lower first molars with apical lesions were randomly divided into two groups: group 1 (15 roots) treated with MTA apical plugs and group 2 (15 roots) treated with Biodentine apical plugs. Treatment radiological outcomes were assessed using the periapical index (PAI) scale after 6 and 12 months of treatment. The presence or absence of apical calcified barrier (ACB) was assessed after 12 months of treatment. The visual analog scale (VAS) was used to compare the postoperative pain between the two groups after 1, 3, 7, and 14 days of treatment. PAI scores between the two groups were compared using the Mann-Whitney U test, the presence or absence of the ACB was compared using the chi-square test, and the VAS scores were compared using the t-test. The statistical significance threshold was set at 0.05. Results: There were no statistically significant differences in the PAI between the two groups at 6 and 12 months postoperatively. After 12 months, four cases in the Biodentine group showed ACB formation, whereas ACB was not found in any case treated with MTA. The VAS scores were statistically lower in the MTA group on the first day after treatment. Nevertheless, these scores were not statistically significantly different after 3, 7, and 14 days of treatment between the two groups. Conclusions: Biodentine can be used as an apical plug to treat immature permanent molars with apical lesions in a single visit in children. Biodentine showed favorable outcomes in apical lesions healing, which was comparable to MTA but with a decreased treatment time associated with its use.